Ortak yetkili mahkemenin kesin yetkili olup olmadığına ilişkin bir değerlendirme (HMK m. 7) - SAÇAR, ÖMER FARUK (My University, 2021)
Davalının birden fazla olması halinde, Hukuk Muhakemeleri Kanunu (HMK) 7. maddesindeki yetki kuralı dikkate alınarak yetkili mahkeme belirlenmektedir. Bu durumda davalılardan birinin yerleşim yeri mahkemesinde dava açılabilir. Ancak kanunda dava sebebine göre davalıların tamamı hakkında ortak yetkiyi taşıyan bir mahkeme belirtilmişse, davaya o yer mahkemesinde bakılır. Bu düzenlemenin kesin yetki kuralı olup olmadığı doktrin ve uygulamada tartışmalıdır. Bu bağlamda ortak yetkili mahkemenin kesin yetkili olup olmadığına ilişkin bir değerlendirme yapılacaktır.

If there is more than one defendant, the competent court is determined by taking into account the rule of competence in Article 7 of the Code of Civil Procedure. In this case, a lawsuit can be filed in the court of the domicile of one of the defendants. However, if a court with joint jurisdiction is specified in the law for all of the defendants according to litigious facts, the case will be heard in the court of that place. Whether this regulation is a exclusive jurisdiction rule is debatable in doctrine and practice. In this article, an evaluation will be made as to whether the joint jurisdiction is exclusive jurisdiction.
An evaluation of whether joint jurisdiction is exclusive jurisdiction
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Medeni Usul ve İcra İflas Hukuku; Social Sciences and Humanities; Law; Law of Civil Procedure and Bankruptcy; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Hukuk; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Competence rules; exclusive jurisdiction; More than one defendant; Article 7 of CCP; Yetki kuralları; Kesin yetki; Birden fazla davalı; HMK madde 7.